Respostas

2014-03-04T19:01:46-03:00
X2+3X-6+8=0
X2 + 3X +2 = 0

a  = 1 , b = 3, c= 2


2014-03-04T20:25:54-03:00
X²+3x-6=-8
x²+3x-6+8=0
x²+3x+2=0                                      2) x = -b + ou -√Δ ÷2         
a=1 ; b=3; c=2                                    x= -3 + ou - √1 ÷2
ax²+bx+c=0                                        x= -3+ ou - 1 ÷ 2
1)Δ=b²-4ac
Δ=3²-4.1.2                                      2.1) x' = -3+1÷2= -2÷2= -1
Δ=9-8                                            2.2) x'' = -3-1÷2= -4÷2= -2
Δ=1
1 5 1